Analysis of the Implementation of the Viseme-Based Method in Ficusia Animation - Zega , Selly Artaty; Filbert, Adric; Tambun , Gerson Julyfer Parulian; Ardhi , Muhammad Fauzi (Universitas Multimedia Nusantara, 2025)
Based on interviews with the Ficusia animation team and professionals from Infinite Frameworks Studios, it was found that the lip and jaw movements in Ficusia were too fast, making them appear less realistic. This study aims to improve the quality of lip-sync animation in Ficusia using the viseme-based method, which allows for more natural lip and jaw movements. The viseme-based method was chosen because it is more suitable for 3D animation, producing smoother lip movements that are better integrated with facial expressions compared to the phoneme-based method, which tends to be rigid. A qualitative case study approach was conducted on the first episode of Ficusia, which contains scenes with predominantly human mouth shapes. Primary data were obtained through interviews with experienced animators and supervisors, while secondary data were gathered from literature. The results show that the viseme-based method can enhance the quality of lip-sync, create more natural animation, and improve the integration between lip movements and character expressions. This method is considered effective by professional animators and is expected to serve as a reference for producing realistic lip-sync in 3D animation. Keywords: 3d animation; blender; lip-synch; viseme-based